Characterizing the acute physiological responses to a simulated artistic swim competition - Viana, E.; Bentley, D. J.; Logan-Sprenger, H. M. (Applied Physiology, Nutrition, and Metabolism, 2018)
The purpose of this study was to investigate the acute changes in acid-base balance in highly trained artistic swimmers (AS) during short (=2:45) and long (>2:45) simulated solo performances. 15 athletes (15.8 ± 0.8 yrs) who competed at the provincial level participated in this study. Following a standardized warm-up, each athlete completed a solo performance assessed by FINA certified judges. Water-resistant HR monitors continuously collected HR data. Capillary blood gas (BG) samples were collected pre and post-routine and analyzed for PO2, PCO2, pH, HCO3- and K+. Blood lactate (BLA) was measured before and 3 min post-routine. Routines were divided into either long or short for analysis. There was a significant increase in PO2 (21.2%, t=-2.4, p=0.02) and PCO2 (2.4%, t=0.7, p=0.48) at the end of the routine. pH decreased significantly by 0.9% (t=4.0, p<0.01) and HCO3- decreased significantly by 12.8% (t=4.2, p<0.01). K+ increased significantly by 6.8% (t=2.4, p=0.03) and BLA increased by 77.2% (t=4.1, p<0.01). There were significant differences between PO2 (t=-2.3, p=0.04) between the long and short routines. However, none of the other BG differed significantly between the long and short routines. The HR mean was 122 bpm andmean RPE of 15. The study results indicate a significant correlation between average HR and PO2 (r=0.55, p=0.03). The main finding is the significant change in acid-base balance after a simulated solo performance, which indicates a significant anaerobic energy contribution. The decreases in pH and HCO3- indicate blood acidification, which likely stems from the repeated apneic exposures. Performance interventions should be aimed at accommodating the decrease in pH and increasing fatigue resistance during AS competitions.